PERAN KOMITMEN ORGANISASIONAL MEMEDIASI PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Utama, I Wayan Bagus Satya; Surya, Ida Bagus Ketut (E-Jurnal Manajemen; Vol 9 No 8 (2020)DO - 10.24843/EJMUNUD.2020.v09.i08.p09, 2020)
The purpose of this study are (1) To explain the effect of job satisfaction on turnover intention, (2) To explain the effect of organizational commitment on turnover intention, (3) To explain the effect of job satisfaction on organizational commitment, (4) To explain the mediating role of organizational commitment the effect of job satisfaction on turnover intention. The population of this research is the employees of PT Cipta Nirwana. The sampling technique uses simple random sampling with a total sample of 47 respondents. The analysis technique used is the path analysis technique (path analysis). This study proves that (1) job satisfaction has a negative and significant effect on turnover intention, (2) organizational commitment has a negative and significant effect on turnover intention, (3) job satisfaction has a positive and significant effect on organizational commitment, (4) organizational commitment partially mediates the effect of job satisfaction on turnover intention. Keywords : turnover intention, organizational commitment, job satisfaction